Trabeculae type of juvenile aggressive ossifying fibroma of the maxilla: Report of two cases - Shalu Rai (Contemporary Clinical Dentistry, 2012)
Juvenile ossifying fibroma (JOF) is a rare controversial fibroosseous lesion affecting the craniofacial skeleton and occurring commonly in children and young adults. It is highly aggressive and has a high tendency to recur. It is distinguished from the adult variant of ossifying fibroma on the basis of age, site, clinical behavior and microscopic appearance. Because of its high recurrence rate, which is 30-58%, complete excision is essential. Early diagnosis will circumvent the necessity of radical treatment. We report a rare case of trabecular JOF of maxilla where a computed tomography scan was taken to further support the characteristic feature of the lesion.